Removal of xenotropic murine leukemia virus by nanocellulose based filter paper. Issue 6 (November 2015) - Asper, M.; Hanrieder, T.; Quellmalz, A.; Mihranyan, A.
Abstract: The removal of xenotrpic murine leukemia virus (xMuLV) by size-exclusion filter paper composed of 100% naturally derived cellulose was validated. The filter paper was produced using cellulose nanofibers derived from Cladophora sp. algae. The filter paper was characterized using atomic force microscopy, scanning electron microscopy, helium pycnometry, and model tracer (100 nm latex beads and 50 nm gold nanoparticles) retention tests. Following the filtration of xMuLV spiked solutions, LRV ≥5.25 log10 TCID50 was observed, as limited by the virus titre in the feed solution and sensitivity of the tissue infectivity test. The results of the validation study suggest that the nanocellulose filter paper is useful for removal of endogenous rodent retroviruses and retrovirus-like particles during the production of recombinant proteins. Graphical abstract: Filter paper composed of 100% naturally derived cellulose nanofibers was shown useful to remove xenotropic murine leukemia virus (MuLV) spiked solutions with LRV ≥ 5.25 as limited by titre of the feed solution and sensitivity of tissue infectivity method.